Homeland as a multi-scalar community: (Dis)continuities in the US security/safety discourse and practice. (February 2022) - Tulumello, Simone; Falanga, Roberto
This article takes steps from the birth and consolidation of "homeland" as the central discursive engine of the US national security enterprise; and takes issue with the dominant scholarly interpretation of the geographical and spatial implications of its emergence in terms of the dissolution of space and spatialization in security policy (Bialasiewicz et al., 2007 : 416). We adopt a multi-scalar approach to exploring security discourse/practice, comparing the performativity of national and global security with the local practice/discourse of public safety—with empirical focus on the case of Memphis (TN). Our main arguments are that the homeland builds on the same performative elements of the emergence and consolidation of a certain conception of "community", as it has become dominant in public safety policymaking at the local scale; and that the homeland/community performativity is the expression of a never-ending movement of production of multi-scalar geographies of the "good" and "evil", made of the coexistence of centrifugal (pushing problems away) and centripetal (incorporating any given outside) dimensions.